The role of agriculture and the agro-processing industry for development in Egypt: An overview - El-Enbaby, Hoda; Figueroa, Jose Luis; ElDidi, Hagar; Breisinger, Clemens (International Food Policy Research Institute, 2016)
In order to complement the ongoing macroeconomic and safety net reforms in Egypt, it is important to foster additional sector-specific economic growth, especially in sectors that are good at creating jobs and reducing poverty. One sector that may help foster socioeconomic development in coming years is agriculture and related agro-processing industries. This paper shows that agriculture in Egypt continues to play a relatively important role in the economy compared to other mid-dle income countries. The sector’s stable growth performance has proved to be a reliable contributor to economy-wide output growth over the past decades. The underlying productivity gains have prevented the country’s food import depend-ency ratio from rising in spite of rapidly growing food demand.